Computerized analysis of acceleration parameter for the non-stress test normal and potentially abnormal fetuses. (16th December 2016) - Li, Guangfei; Zhang, Song; Yang, Lin; Li, Shufang; Wang, Yan; Hao, Dongmei; Yang, Yimin; Li, Xuwen; Zhang, Lei; Xu, Mingzhou
Abstract: Non-stress testing (NST) is the primary method of determining fetal condition during the perinatal period, and as such, has high specificity. However, short-term monitoring and visual inspection of the cardiotocogram demonstrates several limitations in understanding fetal status which can be mistaken as predictors of neonatal asphyxia. Fetal electrocardiography (FECG) is a novel, long-term monitoring method which can reflect more objective and accurate fetal information. This article presents experimental results of four fetal heart rate (FHR) acceleration features of 44 fetuses extracted from FECG. The novelty of this approach lies in its combined use of parameters which can express both duration and amplitude of heart rate acceleration. Results demonstrate that most parameters significantly differ between normal fetuses and fetuses with suspected abnormalities. Results are promising for the identification of a set or parameters which may be used as classifiers to improve the success rate when distinguishing between normal and abnormal fetuses.